Energy, exergy and economic assessments of the dual-mode evaporative cooler for various international climate zones - Kashyap S.; Sarkar J.; Kumar A. (My University, 2025)
The conventional desert cooler is effective for dry seasons and the regenerative evaporative cooler (REC) is an effective device for humid seasons in composite climate zones. Hence, the dual-mode evaporative cooler (a two-in-one device) is an intelligent choice for air conditioning, which can operate in both direct and regenerative modes depending on the seasonal climatic condition. The exergy and economic analyses of this novel device for global climatic conditions are performed to check the suitability in different regions of the world. An experimental prototype of a dual-mode evaporative cooler is developed and tested to validate the simulation model. The effectiveness, coefficient of performance, exergy destruction, exergy efficiency, operating cost, and specific total cost (STC) are evaluated for both (direct and regenerative) modes of operation. The annual and month-wise performances of dual-mode evaporative cooler have been assessed for five cities of international climate zones. The operating cost of both modes is compared by considering electricity charges in different countries. The dual-mode device is compared with the single-mode device as well. The specific cost is similar for both modes in most of the ASHRAE climatic zones. The present study reveals that significant energy and cost savings are possible by using the dual-mode evaporative cooler. Practical application: This article considers the application of a dual-mode evaporative cooler (direct as well as regenerative mode) in different climate zones and, through investigating the exergy and economic performances, allows designers and operators to understand the potential benefits of employing various operating modes in particular climates. © The Author(s) 2021.